2005
DOI: 10.1007/s11249-005-8326-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultraviolet Irradiation on the Interactions between Perfluoropolyether Lubricant and Magnetic Disk Surfaces

Abstract: To tailor the characteristics of molecularly thin lubricant films, magnetic disk surfaces coated with nanometer-thick perfluoropolyether AM3001 lubricant films were irradiated with 184.9 and 253.7 nm ultraviolet (UV) rays. We elucidated the effect of UV irradiation on the interactions between the lubricant and the magnetic disk surface via surface energy, bonded lubricant thickness and lubricant spreading measurements for films with and without UV irradiation. We found that UV irradiation decreased the dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Note that lubricant bonding in this sense does not refer to chemical bonds. For measurement of film thickness using ellipsometry, knowing the optical constants (refractive index n and extinction coefficient k) of the lubricant film and the disk is necessary [7,8]. In these studies, n = 1.30 and k = 0 were used for the lubricant film, and the values measured with the ellipsometer prior to lubricant application were used for the disk [9].…”
Section: Measurement Of Film Compositionmentioning
confidence: 99%
“…Note that lubricant bonding in this sense does not refer to chemical bonds. For measurement of film thickness using ellipsometry, knowing the optical constants (refractive index n and extinction coefficient k) of the lubricant film and the disk is necessary [7,8]. In these studies, n = 1.30 and k = 0 were used for the lubricant film, and the values measured with the ellipsometer prior to lubricant application were used for the disk [9].…”
Section: Measurement Of Film Compositionmentioning
confidence: 99%
“…Nakakawaji et al suggested that the bonding mechanism between PFPE chains and diamond-like carbon (DLC) surfaces was affected by factors other than photoelectrons from the DLC surface [4]. Zhang et al discussed the interaction between the PFPE molecules and the carbon surface after UV irradiation in air [5]. Because of the presence of oxygen, ozone was generated during the UV treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier papers attribute the UV bonding of PFPEs to originate from the underlying substrate via UV-induced photoelectrons emitted by the substrate [1][2][3][4][5][6]. The emitted photoelectrons are assumed to attach to the PFPE molecules causing dissociation (e.g., dissociative electron attachment).…”
Section: Introductionmentioning
confidence: 99%